HUBUNGAN ADVERSITY QUOTIENT (AQ) DENGAN NILAI OSCE PADA MAHASISWA ANGKATAN 2013 FAKULTAS KEDOKTERAN UNIVERSITAS RIAU - Ivon Gemiyani Nafriti Gemiyani; Enikarmila Asni; M. Yulis Hamidy (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Adversity Quotient (AQ) is the most scientifically robust and widely used method in the world for measuring and strengthening human resilience. It is beneficial to upgrades particularly on students’ academic performance, which is shown by evaluation achievement. Most of medical schools in the world using assessment method named OSCE to evaluate their students’ clinical skills, including Medical Faculty of Riau University. This is an analytic cross-sectional study, on purposed to determine the correlation between Adversity Quotient and OSCE achievement of medical students of Riau University on year 2013. About 112 medical students of Riau University, obtained by total sampling method, have been selected as samples. Primary data was taken by using Stolzt’s based theory questionnaire and secondary data was available as OSCE mark form. Data processed by using correlation test Spearman to discovered correlation between AQ and OSCE achievement. Results showed there was a significant and poor correlation between Adversity Quotient and OSCE achievement (p=0.033;r=0.202), which was leading to a conclusion: the higher level of AQ reached, the higher OSCE score can be achieved.Key words: Adversity Quotient, OSCE achievement, medical students